Development of New Gluten-Free Maize-Field Bean Bread Dough: Relationships Between Rheological Properties and Structure of Non-Gluten Proteins - Awatif Fetouhi; Agnieszka Sujak; Leila Bentallah; Agnieszka Nawrocka; Monika Szymańska-Chargot; Marta Tomczyńska-Mleko; Agnieszka Wójtowicz; Mohammed Nasreddine Zidoune (Polish Journal of Food and Nutrition Sciences)
This work aimed to examine the rheological properties and structural features of newly developed gluten-free doughs with maize (M), field bean (FB), maize-filed bean (MFB), and maize-field bean improved with hydrothermally-treated maize (IMFB), and compare them with soft wheat (SW) dough as a control. The relationships between viscoelastic characteristics, pasting properties of dough, and structure of non-gluten proteins analyzed using FT-Raman spectroscopy were investigated. All gluten-free doughs showed significantly higher values of the elastic modulus than SW dough. The low values of tan δ for doughs of M, MFB, and IMFB formulas indicated strong contribution of the solid character in their structural formation as compared to SW and FB doughs. Protein backbone of maize and maize-based doughs was characterized by the absence of pseudo-β-sheet structure and a high content of β-sheet accompanied with a low content of antiparallel-β-sheet. According to principal component analysis (PCA), a strong relationship was found between protein secondary structure, tan δ, gelatinization temperature, and between aromatic amino-acid chains, peak viscosity, and breakdown. The mechanism of non-gluten protein network establishment was based on the formation of β-sheet and α-helix structure. The study results indicate the significant involvement of trans-gauche-gauche (TGG) and trans-gauche-trans (TGT) disulfide bridges in the formation of the non-gluten protein matrix rather that gauche-gauche-gauche (GGG) conformation. PCA analysis showed that the water absorption of the starch granules increased with the greater exposition of the tyrosyl residues.